2018
DOI: 10.1016/j.ijedudev.2017.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Regulating market entry of low-cost private schools in Sub-Saharan Africa: Towards a theory of private education regulation

Abstract: This study provides a comparative assessment of policies governing private schools in twenty countries in Sub-Saharan Africa. Findings suggest that current regulatory systems are failing to adequately address the negative externalities and failures of private schooling markets. Insufficient capacity on the part of governments is a contributor to uneven policy implementation and creates opportunities for rentseeking and corruption. Onerous market entry regulations offer constraints on the growth of official pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…There needs to be more analysis on what constitutes sensible regulations for private schooling to incentivize registration (Baum et al 2018) as a private school or as a tutoring center. The research shows that there is ease of entry in providing private schooling or tutoring in several South Asian contexts.…”
Section: Discussion: Unresolved Issues When Taking a Systemic Perspecmentioning
confidence: 99%
“…There needs to be more analysis on what constitutes sensible regulations for private schooling to incentivize registration (Baum et al 2018) as a private school or as a tutoring center. The research shows that there is ease of entry in providing private schooling or tutoring in several South Asian contexts.…”
Section: Discussion: Unresolved Issues When Taking a Systemic Perspecmentioning
confidence: 99%
“…In the short-term, the government may do well to focus on quality assurance in regards to the LFPS preschools that are mushrooming around Lusaka, in addition to step-by-step expansion of public provision with quality. That said, research has shown the limited ability of governments to adequately oversee the private school sector and to provide these kinds of support (Baum, Cooper, & Lusk-Stover., 2018;Harma, 2019). At the moment, these low cost private preschools function without any monitoring or support from the MoGE.…”
Section: Low-fee Private Schools the State And Globalizationmentioning
confidence: 99%
“…In connection to such findings, a range of researchers have showed that the emergence of low-cost and low-quality private schools for the poor are likely to reinforce and deepen school segregation (for an overview of these debates, see Macpherson, 2014). Finally, different authors have addressed the shortcomings of the LFPS modality in relation to regulatory practices, and recent accounts have made it clear that the nature, quality and effective application of existing regulations is a key element explaining the specific characteristics of LFPSs in different contexts (Baum, Cooper, & Lusk-Stover, 2018;Härmä, 2019).…”
Section: Researching Low-fee Private Schools: Recent Advances and Blimentioning
confidence: 99%